Residual aqueous fraction of Ethulia conyzoides L. extract regulates liver and kidney functions and prevents pancreatic β-cells damage in high fat diet-streptozotocin Type 2 diabetes in Rats - Wusa Makena; Helen Omasan Okotie; Nathan Isaac Dibal; Barka Ishaku; Sebastine Anthony Bazabang (Ntec Specialist, 2022)
Background: Complications of Type 2 Diabetes (T2D) include hypertension, oxidative stress, liver disease, and kidney disease. These complications are the main cause of death and disability in diabetic patients. Objective: The study investigated the effect of residual aqueous fraction of Ethulia conyzoides L. extract on liver and kidney function as well as the histology of liver, kidney, and pancreatic islets of type 2 diabetic rats. Methodology: Thirty-six rats were divided into six groups (n=6). Group I (non-diabetic rats) and II (diabetic control) were given feed and water only. Groups III-V were treated with 100mg/kg, 200mg/kg, and 400mg/kg Ethulia conyzoides L. while group VI received 100mg/kg metformin for 28 days. The liver and kidney function were evaluated while the liver, pancreas, and kidney were processed for light microscopy. Results: A significant reduction (P less than 0.05) in total protein and albumin levels were observed in diabetic control rats when compared with diabetic rats treated with 400mg/kg Ethulia conyzoides L. A significant decrease in high-density lipoprotein was observed in diabetic control rats when compared with diabetic rats treated with Ethulia conyzoides L. The liver and kidney of diabetic rats treated with Ethulia conyzoides L. showed normal hepatocytes/central vein and glomerulus respectively. The pancreatic islet of diabetic control rats treated with Ethulia conyzoides L. showed near-normal positive staining of insulin/β-cell by insulin antibody. Conclusion: Ethulia conyzoides L. prevented liver and kidney damage in Type 2 diabetic rats by improving liver and kidney functions and maintaining the normal pool of pancreatic β-cells.